Proteomic scrutiny of ’triton-x-114 sediment’ of mycobacterium tuberculosis H37RV membrane fraction, to complement ’triton-x-114 proteome’ of m. Tuberculosis. - VINEET K. MAURYA; SUDHIR K. SINHA (International Journal of Pharma and Bio Sciences, 2017)
Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb), is one of the deadliest diseases known to mankind, it claimed 10.4 million new infections and 1.8 million deaths in 2015. Any new drug or vaccine has not been developed for TB since last 50-60 hence new anti-TB drugs /vaccines are urgently required. Analysis of Mtb proteome using proteomics techniques offers good scope for development of new anti-TB drugs and/or vaccines. Mtb proteome can be divided into three parts; cytosole, membrane and cell wall. Due to inherent difficulties membrane proteome is lesser explored compared to others. But due to their paramount structural and functional importance, membrane proteins are supposed to serve as potential drug targets, hence scientists are exploring them too. Trtiton-X-114 fractionation is widely accepted technique for analysis of membrane proteins. This technique provides 3 subfractions; detergent phase (DP), aqueous phase (AP) and detergent insoluble Triton-X-114 sediment (TX14-SD). DP and AP have been already analyzed by our lab hence remaining TX14-SD was focused to complement the Triton- X-114 proteome of Mtb. Using 2D- GE proteomic approach 18 proteins were identified from 26 spots, picked form 2D gel of TX14-SD. All 18 spots were identified with significant MOWSE score and 55.5% of them were having GRAVY score <0.4 indicating their association with cell membrane. Although none of them was having trans-membrane domain, which is indicator of membrane protein but their presence in membrane fraction shows their association with membrane proteins. Twelve proteins were identified for first time in this study using 2D-GE. Although no any new protein was identified in triton sediment, but present study complemented the Triton-X-114 proteome of Mtb and confirmed the efficacy of triton-X-114 fractionation in enriching all the membrane proteins in detergent phase, leaving TX14-SD devoid of them.